Potensi Teh Herbal sebagai Penghambat α-Amilase dan α-Glukosidase dalam Pengelolaan Diabetes Melitus Tipe 2: Tinjauan Literatur - Annisa Nofriani; Naura Nurnahari; Mubarika Sekarsari Yusuf (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Type 2 diabetes mellitus is a metabolic disorder with a steadily increasing global prevalence. Regulating blood glucose levels, particularly postprandial glucose, represents a critical strategy for the prevention and management of this disease. The inhibition of α-amylase and α-glucosidase activities is well-documented to delay carbohydrate digestion and subsequent glucose absorption. In recent years, herbal teas have gained significant attention as natural sources of bioactive compounds with potential antidiabetic properties. This literature review aims to evaluate the potential of various herbal teas, derived from both Camellia sinensis and non-Camellia sinensis species, in inhibiting α-amylase and α-glucosidase activities, based on in vitro studies published between 2016 and 2026. Relevant literature was gathered through systematic searches across PubMed and Google Scholar databases and further screened according to predefined inclusion criteria. A total of 26 articles were analyzed to evaluate enzyme inhibitory activities, the responsible bioactive compounds, and their reported mechanisms of action. The findings indicate that white and green teas exhibit potent α-glucosidase inhibitory activity, primarily attributed to their catechin content, such as epigallocatechin gallate (EGCG) and epicatechin gallate (ECG). Furthermore, black, oolong, and dark teas, along with various polyherbal formulations, also demonstrated significant enzyme inhibition. Generally, polyphenols and other phenolic compounds serve as the primary constituents contributing to this biological activity. These findings suggest that herbal teas have the potential to be developed as an adjuvant therapy in the management of type 2 diabetes mellitus, although further in vivo studies and clinical trials remain essential to confirm their efficacy and safety.